Institutionalisation of Scandinavian Consensual Democracy - Musiał, Kazimierz (Folia Scandinavica Posnaniensia, 2007)
The paper takes as a point of departure the notion of consensual democracy as a characteristic element of the so called Scandinavian Model. Both terms, i.e. the consensual democracy and the Scandinavian Model got really famous only after World War Two as potential Scandinavian ‘export goods’. The author argues that singularity of Scandinavian solutions within the labour market and politics started already before World War Two. The key to understanding the origin of the Scandinavian Model lies in understanding of the nature of collective bargaining in the Nordic countries. The September Agreement of 1899 in Denmark and the Saltsjobaden Agreement of 1938 in Sweden are examples of institutionalisation of labour relations, while the Danish Kanslergade Agreement and the Swedish Kohandel of 1933 are instances taken from parliamentary politics. These examples show how the pattern for conflict resolution in the Scandinavian countries was institutionalised.